Rheology : an historical perspective - Tanner, Roger I. (Rheology series, 1998)
The science of rheology remains a mystery to most people, even to some scientists. Some respectable dictionaries have been quite cavalier in their attitude to the science, the small Collins Gem dictionary, for example, being quite happy to inform us that a Rhea is an three-toed South American ostrich, whilst at the same time offering no definition of rheology. This maybe due to the fact that the science is interdisciplinary and does not fit well into any one of the historical disciplines. This book contains an in-depth study of the history of rheology, beginning with the statements of Heraclitus, Confucius and the prophetess Deborah. It also emphasises the distinctive contributions of Newton, Hooke, Boltzmann, Maxwell, Kelvin and others, and culminates in the flourishing activity in the second half of this century. Features of this book: & bull; Is the only book on the subject & bull; Prevents the rediscovery of results already made & bull; Will educate newcomers to the field to the rich heritage in even a relatively recent science like rheology. The book will be invaluable for science and scientific history libraries and will also be of interest to rheologists, and scientists working in the polymer processing, food, lubrication, detergent and similar industries.